The Development of Reading Skill Teaching Materials Based on Prezi Artificial Intelligence - Khuluq, Muchsinul; Ainin, Moh.; Rosyidi, Abdul Wahab; Imamah, Nurul (Arabiyatuna: Jurnal Bahasa Arab, 2025)
This study aimed to develop more engaging and effective teaching materials of maharah qiroah (reading skills) for tenth-grade students in Indonesia through the utilization of the Prezi Artificial Intelligence application. The development was driven by the limitations of conventional textbooks that in many ways appeared monotonous and unengaging. Using a qualitative Research and Development (R&D) approach with the 4D model, this study employed the Qiroah Muqhatta’ah strategy, breaking texts into manageable fragments to enhance comprehension. The materials were tested on 20 students with Novice-level Arabic proficiency. The results showed a significant improvement in reading comprehension, with average scores rising from 56.3 (pre-test) to 77.5 (post-test), and 85% of students reporting increased engagement. Observations revealed greater confidence and interaction, especially with the use of visuals and zooming features. However, challenges such as limited internet access and low digital literacy among students were noted. This study suggests that while Prezi AI offers considerable benefits, its effectiveness depends on contextual factors such as infrastructure and teacher facilitation.